OPTIMIZATION OF GASOLINE METHANOL ETHANOL (GME) SUPPLY CHAIN NETWORK DESIGN USING MIXED INTEGER LINEAR PROGRAMMING - Firdaus, Azzimar
Gasoline needs in Indonesia has been constantly increasing throughout the year. Domestic production capacity is relatively constant and could not fulfill all demands hence decided to import gasoline. To reduce gasoline import, the government is currently proposing Gasoline Methanol Ethanol (GME) as a new energy source. GME is a blend of gasoline, methanol, and ethanol, mixed with specific compositions and additives. A key consideration for implementing GME is its supply chain.